Kinetics of permeation and absorption of hydrogen in palladium during bending and unbending of a palladium cantilever - Feldman, E. P.; Lyubimenko, E. N.; Gumennyk, K. V. (Journal of applied physics, 2020)
The paper gives an analytical solution for the practically important problem of finding the magnitude of the mechanical deflection of a thin palladium plate (cantilever) during its one-sided saturation with hydrogen. A reasonably simple model is proposed, which permits us to derive and analyze a system of kinetic equations defining the concentration gradient of atomic hydrogen across the plate. We perform numerical integration and asymptotic analysis of the obtained governing equations (subject to acceptable initial and boundary conditions) and thus describe the temporal evolution of the deflection. The latter is found to be in good agreement with time dependence of a palladium cantilever bending obtained in the experimental part of the work. These results permit us to determine an important kinetic coefficient, namely, the permeation rate of hydrogen through the palladium surface.